Ethnicity, Identity, And The Politics Of Space In Urban Society Of Jayapura City - Akhmad, Rosye; Tanjung, Rosye H.R; Poli, Agustina Ivonne; Ali, Aisyah; Kumoro, Nindyo B. (Advances in Social Sciences Research Journal, 2019)
Despite the Special Autonomy Law has been declared, ethnical sentiment between migrant settlers (amber) and indigenous of Papua (komin) is still strong in Jayapura society. This study assumes that primordial sentiment does not merely derive from cultural differences, yet it is more likely caused by the social-economical disparities, mainly access to the venture space resources. Thereby, this study attempts to investigate how economic spatial domination upon Jayapura city between settlers and Papuans and what are the affecting factors? Using the urban ethnography method, we argue that settlers-indigenous sentiment grew as urban economic structure had not been really changed since the colonial era, even until Special Autonomy implementation. Those settlers such Chinese, Buginese, or Javanese subdue economical opportunities of the city. While Papua communities have not fully integrated to the market economy due to political history which tied up to the traditional manner. However, state affirmative politic after the Special Autonomy Law symbolically delivers new strength for Papuans in negotiating towards economic space disparities of Jayapura.